LAMP-2 deficiency leads to hippocampal dysfunction but normal clearance of neuronal substrates of chaperone-mediated autophagy in a mouse model for Danon disease - Rothaug, Michelle; Stroobants, Stijn; Schweizer, Michaela; Peters, Judith; Zunke, Friederike; Allerding, Mirka; D'Hooge, Rudi; Saftig, Paul; Blanz, Judith (Acta Neuropathologica Communications, 2015)
The Lysosomal Associated Membrane Protein type-2 (LAMP-2) is an abundant lysosomal membrane protein with an important role in immunity, macroautophagy (MA) and chaperone-mediated autophagy (CMA). Mutations within the Lamp2 gene cause Danon disease, an X-linked lysosomal storage disorder characterized by (cardio)myopathy and intellectual dysfunction. The pathological hallmark of this disease is an accumulation of glycogen and autophagic vacuoles in cardiac and skeletal muscle that, along with the myopathy, is also present in LAMP-2-deficient mice. Intellectual dysfunction observed in the human disease suggests a pivotal role of LAMP-2 within brain. LAMP-2A, one specific LAMP-2 isoform, was proposed to be important for the lysosomal degradation of selective proteins involved in neurodegenerative diseases such as Huntington's and Parkinson's disease. To elucidate the neuronal function of LAMP-2 we analyzed knockout mice for neuropathological changes, MA and steady-state levels of CMA substrates. The absence of LAMP-2 in murine brain led to inflammation and abnormal behavior, including motor deficits and impaired learning. The latter abnormality points to hippocampal dysfunction caused by altered lysosomal activity, distinct accumulation of p62-positive aggregates, autophagic vacuoles and lipid storage within hippocampal neurons and their presynaptic terminals. The absence of LAMP-2 did not apparently affect MA or steady-state levels of selected CMA substrates in brain or neuroblastoma cells under physiological and prolonged starvation conditions. Our data contribute to the understanding of intellectual dysfunction observed in Danon disease patients and highlight the role of LAMP-2 within the central nervous system, particularly the hippocampus.
CRIS-Team Scopus Importer:2020-10-21